1995
DOI: 10.1161/01.res.76.6.1028
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I Phosphorylation Increases the Rate of Cardiac Muscle Relaxation

Abstract: Cardiac troponin (Tn) I (CTnI), compared with skeletal TnI, contains extra amino acids (32 to 33) at its amino terminus, including two adjacent serine residues. These two serine residues are believed to be phosphorylated by protein kinase A (PKA) upon stimulation of the heart by beta-agonists. In this study, we found that phosphorylation of a cardiac skinned muscle preparation by PKA, mainly at CTnI, results in a decrease in the Ca2+ sensitivity of muscle contraction. The pCa50 decreased by approximately 0.27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
254
6
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(284 citation statements)
references
References 36 publications
20
254
6
4
Order By: Relevance
“…The simulations suggested a desensitization of the myofilament to calcium in Pkd2 +/− mice under baseline conditions, which is a known effect of TnI phosphorylation (28). Consistent with our model, we found that the phosphorylation status of TnI at the PKA phosphorylation site Ser22/23 in Pkd2 +/− mice was 90% higher than in WT mice (Fig.…”
Section: Resultssupporting
confidence: 88%
“…The simulations suggested a desensitization of the myofilament to calcium in Pkd2 +/− mice under baseline conditions, which is a known effect of TnI phosphorylation (28). Consistent with our model, we found that the phosphorylation status of TnI at the PKA phosphorylation site Ser22/23 in Pkd2 +/− mice was 90% higher than in WT mice (Fig.…”
Section: Resultssupporting
confidence: 88%
“…3A shows that after PKA treatment the Ca 2+ sensitivity of the fibres reconstituted with wild-type TnI was significantly reduced by 0.22 pCa units (from 5.35 + 0.015 to 5.13 + 0.04, n = 5). This change in Ca 2+ sensitvity induced by PKA was similar to that observed by others [9].…”
Section: ? Effect Of Extraction and Reconstitution Of Tni And Tncsupporting
confidence: 91%
“…In the heart, phosphorylation of TnI by PKA occurs following fladrenergic stimulation [17] and may be considered as an adaptive mechanism to prevent overstimulation. The phosphorylation of cardiac TnI has been shown to reduce the affinity of TnC for Ca 2+ [18], thus, promoting more rapid relaxation [9]. Different TnI isoforms from various tissues have been overexpressed in bacterial systems [19,20] and a number of mutants have been produced in order to investigate the structur~func-tion relationship in TnI [7,10,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The HCTnI mutants (R145G and A86T,R145G) were formed by overlapping PCR using HCTnI cDNA previously cloned in our laboratory from human cardiac tissue (23). The sequence of the TnI mutants was verified by sequencing prior to expression and purification.…”
Section: Mutation Expression and Purification Of Hctni And Hctni R1mentioning
confidence: 99%
“…Preparation of Porcine Skinned Cardiac Muscle Bundles-Cardiac skinned muscle fibers were prepared following a common laboratory procedure published by Zhang et al (23). Freshly isolated porcine hearts were incubated in an O 2 -saturated solution containing 140 mM NaCl, 4 mM KCl, 1.8 mM CaCl 2 , 1 mM MgCl 2 , 1.8 mM NaHPO 4 , 5.5 mM glucose, and 5 mM HEPES, pH 7.4.…”
Section: Mutation Expression and Purification Of Hctni And Hctni R1mentioning
confidence: 99%